REFRIGERATION OF CANINE SEMEN USING GLUCOSE, FRUCTOSE, TREHALOSE OR SUCROSE TO EXTEND SPERM SURVIVAL - Flores A., Jonathan (2010)
The effect of glucose, fructose, trehalose, and sucrose, as components of the extender, was evaluated on canine sperm viability during refrigeration at 5 ºC. The spermatic fraction of 16 dog ejaculations were distributed in 5 aliquots containing an extender based on Tris – citric acid – egg yolk, but differing in the presence of one of the sugars, plus a control without sugar. The five treatments were evaluated after 24, 48, 72, and 96 hours of refrigeration in relation to progressive motility and functional integrity of the membrane by the hypoosmotic swelling test (HOS). All groups, with the exception of the control group, the sperm motility maintained within acceptable ranges during the study (90% on day 0 and 60% on day 4). The integrity of the membrane remained slightly superior in groups with sugar (87-90%) in comparison with the control group (83-85%). The glucose and sucrose showed the best results in motility and HOS. It is concluded that no significant damage occurred on the sperm membrane while keeping semen at 5 ºC, and that the use of any of the tested sugars as energy-giving substrate for the sperm cells (especially glucose and sucrose) is of great importance for the maintenance of appropriate levels of sperm motility and functional integrity of the membrane.